2018
DOI: 10.1051/matecconf/201815006027
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between learning capabilities and organizational performance: The mediating role of organizational innovativeness

Abstract: This paper investigates the Organizational Learning Capabilities (OLC) affect Organizational innovativeness (OI) on organizational performance (OP). The mediating role of IO on relationship between OLC and OP was also been studied. Analysis is based on data collected from 200 respondents drawn from Pakistan’s Telecom Sectors. Multiple regression analysis had been used to test the hypotheses. This study found that both OLC and OI have a positive impact towards OP. OI also mediates the relationship between OLC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…As the results showed, learning organizational has a positive impact on innovation. In line with our results, (Abdi et al , 2018; Hussain et al , 2018) have also proven that learning has a positive impact on innovation. As a teacher and learner, learning is growing rapidly.…”
Section: Discussionsupporting
confidence: 92%
“…As the results showed, learning organizational has a positive impact on innovation. In line with our results, (Abdi et al , 2018; Hussain et al , 2018) have also proven that learning has a positive impact on innovation. As a teacher and learner, learning is growing rapidly.…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted on manufacturing and service sector firms in Ethiopia confirmed that organizations that have access to information, own skilled workforce, offer training and conduct R&D are more likely to innovate than their counterparts (Daksa et al, 2018). Similar studies conducted on manufacturing firms in Jordan (Karasneh, 2019), telecom firms in Pakistan (Hussain et al, 2018), ICT industry in Malaysia (Salim and Sulaiman, 2011) and textile industry in Brazil (Gomes and Wojahn, 2016;Tambosi et al, 2020) have discovered the positive effect of OLC on innovations conducted in organizational settings. However, apart from reporting the effect of OLC on OI, none of the above studies have examined the studied organizations with respect to their level of learning and innovation.…”
Section: Organizational Learning Capability and Organizational Innova...mentioning
confidence: 83%
“…All the study constructs factor loadings are ranging from .566 to .898. As earlier used by various researchers , Javaid et al (2018), Hussain et al (2018) and , various statistical analyses were employed in this study.…”
Section: Sample and Proceduresmentioning
confidence: 99%